2021
DOI: 10.1080/19490976.2021.2014739
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function SLC30A2 mutants are associated with gut dysbiosis and alterations in intestinal gene expression in preterm infants

Abstract: Loss of Paneth cell (PC) function is implicated in intestinal dysbiosis, mucosal inflammation, and numerous intestinal disorders, including necrotizing enterocolitis (NEC). Studies in mouse models show that zinc transporter ZnT2 ( SLC30A2 ) is critical for PC function, playing a role in granule formation, secretion, and antimicrobial activity; however, no studies have investigated whether loss of ZnT2 function is associated with dysbiosis, mucosal inflammation, or intestinal dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…A role for ZnT2 in intestinal health in humans has been previously proposed as genetic variants in ZnT2 have been associated with alterations in the gut microbiome and gene expression in the intestinal exfoliome [ 11 ]. A compound substitution in the C-terminus (Exon 7) [ 35 ] impairs Zn transport and is associated with enrichment of nosocomial bacteria and enrichment in intestinal genes associated with cell proliferation and remodeling [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A role for ZnT2 in intestinal health in humans has been previously proposed as genetic variants in ZnT2 have been associated with alterations in the gut microbiome and gene expression in the intestinal exfoliome [ 11 ]. A compound substitution in the C-terminus (Exon 7) [ 35 ] impairs Zn transport and is associated with enrichment of nosocomial bacteria and enrichment in intestinal genes associated with cell proliferation and remodeling [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A role for ZnT2 in intestinal health in humans has been previously proposed as genetic variants in ZnT2 have been associated with alterations in the gut microbiome and gene expression in the intestinal exfoliome [ 11 ]. A compound substitution in the C-terminus (Exon 7) [ 35 ] impairs Zn transport and is associated with enrichment of nosocomial bacteria and enrichment in intestinal genes associated with cell proliferation and remodeling [ 11 ]. A second ZnT2 variant (L 293 R) also predicted to impair Zn transport is associated with profound gut dysbiosis, changes in intestinal gene expression consistent with inflammation, and poor growth in preterm infants [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCs are housed in the crypt of the intestine and secrete antimicrobial peptides (AMPs), which are known to defend against pathogen infection ( 36 , 37 ). Furthermore, PCs also play an essential role in intestinal homeostasis and microbiome colonization; for example, loss of PC function is implicated in microbiome dysbiosis and NEC in early life ( 38 , 39 ). It has been found that Cdk5rap3 (a gene that serves a vital role in intestinal PC development and maintenance) knockout resulted in early embryonic lethality, which indicated that embryonic PC function may determine the embryo fate ( 40 ).…”
Section: Intestinal Innate Immune System Developmentmentioning
confidence: 99%
“…Genetic variation can reshape the structure of the gut microbiota. Mutation in human SLC30A2 leads to reduced intestinal zinc transport and increased Clostridiales and Bacteroidales abundance, causing mucosal inflammation and intestinal dysfunction (Kelleher et al, 2022). Moreover, the gut GLUT1 gene deletion altered the abundances of Barnesiella intestinis and Faecalibaculum rodentium , promoted fat accumulation, and impaired sugar tolerance (He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%